2024
DOI: 10.2174/1567201820666230518161330
|View full text |Cite
|
Sign up to set email alerts
|

Oral Insulin Delivery: A Review on Recent Advancements and Novel Strategies

Abstract: Background: Due to the lifestyle of people in the community in recent years, the prevalence of diabetes mellitus has increased, so New drugs and related treatments are also being developed. Introduction: One of the essential treatments for diabetes today is injectable insulin forms, which have their problems and limitations, such as invasive and less admission of patients and high cost of production. According to the mentioned issues, Theoretically, Oral insulin forms can solve many problems of injectable fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…Oral insulin delivery has been attempted using lipid-based, synthetic polymer-based, and polysaccharide-based nano/microparticle formulations. Although insulin-transporting particles may preserve insulin in the acidic and enzymatic medium and decrease peptide degradation, in vivo results revealed a lower ability of formulations to reduce glucose in the blood than the subcutaneous form despite promising in vitro results [146].…”
Section: Recent Formulations For Antimicrobial Peptidesmentioning
confidence: 99%
“…Oral insulin delivery has been attempted using lipid-based, synthetic polymer-based, and polysaccharide-based nano/microparticle formulations. Although insulin-transporting particles may preserve insulin in the acidic and enzymatic medium and decrease peptide degradation, in vivo results revealed a lower ability of formulations to reduce glucose in the blood than the subcutaneous form despite promising in vitro results [146].…”
Section: Recent Formulations For Antimicrobial Peptidesmentioning
confidence: 99%
“…Studies have shown that the dissociation of the nanoparticulate structure could happen due to the deprotonation or protonation of particle components (such as polysaccharides, proteins, or lipids) in different pH environments, resulting in the burst release and degradation of encapsulated bioactive compounds. Hence, good GI-stability of nanoparticles across a wide range of pH values is crucial to protect insulin throughout the entire GI transition against chemical degradation and improve its oral bioavailability [ 23 ].…”
Section: Introductionmentioning
confidence: 99%